PH‐Dependent hydrolase, glutaminase, transpeptidase and autotranspeptidase activities of Bacillus subtilis γ‐glutamyltransferase. (26th November 2013) - Morelli, Carlo F.; Calvio, Cinzia; Biagiotti, Marco; Speranza, Giovanna
<x xml:space="preserve">Abstract</x> γ‐Glutamyltransferases (γ‐GTs) are heterodimeric enzymes that catalyze the transfer of a γ‐glutamyl group from a donor species to an acceptor molecule in a transpeptidation reaction through the formation of an intermediate γ‐glutamyl enzyme. In our search for a γ‐GT from a generally recognized as safe microorganism suitable for the production of γ‐glutamyl derivatives with flavor‐enhancing properties intended for human use, we cloned and overexpressed the γ‐GT from Bacillus subtilis. In this study, we report the behavior of B. subtilis γ‐GT in reactions involving glutamine as the donor compound and various acceptor amino acids. The common thread emerging from our results is a strong dependence of the hydrolase, transpeptidase and autotranspeptidase activities of B. subtilis γ‐GT on pH, also in relation to the pKa of the acceptor amino acids. Glutamine, commonly referred to as a poor acceptor molecule, undergoes rapid autotranspeptidation at elevated pH, affording oligomeric species, in which up to four γ‐glutamyl moieties are linked to a single glutamine. Moreover, we found that d‐glutamine is also recognized both as a donor and as an acceptor substrate. Our results prove that the B. subtilis γ‐GT‐catalyzed transpeptidation reaction is feasible, and the observed activities of γ‐GT from B. subtilis could be interpreted in relation to the known ability of the enzyme to process the polymeric material γ‐polyglutamic acid.